Laboratory tests in rigid pavement - Rasol, Mezgeen A. (2019)
Deterioration of concrete structure is consequence of aging, applied loads and weathering. In this paper, several laboratory tests were presented, compared to computational models and a field test case study. The purpose of the laboratory measurements is the analysis of the results in the case of different size cracks in concrete beams, filled with several materials.